2021
DOI: 10.3389/fpubh.2021.737278
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Transaction Process With Doctors on Patient Satisfaction, Self-Rating Anxiety and Self-Efficacy Among International Students in China

Abstract: Objectives: To investigate the communication mechanism between international students and Chinese physicians by evaluating the influence of the transaction process on patient satisfaction, self-rating anxiety and self-efficacy.Methods: A cross-sectional survey was conducted among international students living in Central, Northern and Eastern China; enrolled at Chinese universities and experienced outpatient and inpatient healthcare services. Guided by the elements of King's transaction process: IR, Initiating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This study makes several methodological and theoretical contributions. First, in terms of methodology, previous studies on patient satisfaction have used cross-sectional questionnaires and descriptive studies (69,70), which may be geographically limited and make it difficult to establish a causal relationship between determinants and satisfaction. Second, many studies related to recommendation sources [e.g., (19,20)] have shown that online consumer reviews are the main source of information for consumers' decisions.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…This study makes several methodological and theoretical contributions. First, in terms of methodology, previous studies on patient satisfaction have used cross-sectional questionnaires and descriptive studies (69,70), which may be geographically limited and make it difficult to establish a causal relationship between determinants and satisfaction. Second, many studies related to recommendation sources [e.g., (19,20)] have shown that online consumer reviews are the main source of information for consumers' decisions.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The professional values of good doctors strengthen their conviction to rescue the dying and heal the wounded, ensure that their behaviours are in line with their aspirations, and enhance their professional morality, passion, dedication, and devotion to medicine. Driven by such a strong value, good doctors will focus more intensively on all the endeavours mentioned above by sharpening their abilities to do so and perfect their skills and competence; moreover, professional values will increase their sense of gain, help them recognize their contribution to medical causes, and continuously propel them to engage in more high-performance behaviours [ 39 ] to maintain an unswerving commitment to making innovations and breakthroughs, love their work, and improve their health.…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported SCL-90, clinician-related HAM-A, and HAM-D are all widely used mental questionnaires in China, which are reported to have great potency in screening mental health, diagnosing, and estimating mental illness ( 22 24 ). In China, previous studies on SCL-90 focused primarily on students, doctors, nurses, police, and migrant workers, among others ( 24 27 ).…”
Section: Discussionmentioning
confidence: 99%